Enhancing the resilience of supply chains in the fashion apparel industry through intelligent logistics—evidence from China - Junjie Cai; Ismawati Sharkawi; Shairil Izwan Taasim (Cogent Business & Management)
Enhancing the resilience of supply chains is a key factor in ensuring economic circulation and social development. This study examines the impact of intelligent logistics on the resilience of supply chains in the fashion apparel industry, based on data from prefecture-level cities in China and A-share listed fashion apparel companies from 2008 to 2021. The findings show that intelligent logistics significantly enhance both the resistance and recovery capabilities of supply chains, promoting an overall improvement in supply chain resilience. The key mechanisms include expanding corporate market strategies, reducing transaction costs, and improving supply chain efficiency. This study not only broadens the research field of intelligent logistics’ impact on supply chain resilience but also provides valuable references for the Chinese government to optimize relevant policies.